(untitled) (Journal of Global Accounting, 2025)
This study examined entrepreneurial innovation as an effective tool for poverty alleviation in Federal Capital Territory (FCT), Abuja. A survey research design was adopted, and a structured questionnaire was used to elicit response from a sample of 109 respondents, selected through a purposive sampling technique to ensure the inclusion of individuals with relevant experiences in entrepreneurship. The data sourced was subjected to analysis in both descriptive statistics using percentages, and inferential statistics using regression tool from Statistical Product for Social Science (SPSS) version 27. The findings indicated that entrepreneurial innovation significantly contributes to creating employment opportunities for residents of FCT Abuja. The results of the one-sample t-test demonstrated a substantial mean difference from the assumed mean of zero, with a t-value of 23.650 and a significance level of p<0.001. Additionally, the study found that entrepreneurial innovation improved access to basic services for residents, evidenced by a t-value of 19.499 and a mean difference of 89.000. The t-test results supported this assertion, with a t-value of 17.504, indicating that innovative practices fostered economic resilience and reduced vulnerability among residents. The findings highlighted that entrepreneurial ventures were crucial in diversifying income sources and promoting sustainable economic growth, thereby contributing to poverty alleviation in FCT Abuja. Policymakers and stakeholders are encouraged to support initiatives that promote entrepreneurial innovation, as these efforts could lead to sustainable development and improved living standards for residents in the region